Appropriate Building Materials for Facades and Interiors of Railway Stations (Journal of Architectural Design, 2022)
All trips by rail, as a rule, begin and end in the station building. Following the psychology of the passenger, it is easy to understand his desire as quickly as possible, entrusts himself to the care of the railway service, to get to his destination. At the dawn of the railways, efforts were required to attract passengers. Concerts and various celebrations were held in the buildings of the railway stations. This left a peculiar imprint on the stylistic features of the railway stations being built at that time, which more resembled palaces than office buildings